Vanadium-based lithium-loving composite framework lithium metal negative electrode and preparation method thereof

By modifying the nanovanadiode-based lithium-philic material on the skeleton interface of the lithium metal negative electrode, regulating the growth of lithium metal, the problem of dendrites and dead lithium accumulation is solved, the cycle stability and life of lithium metal batteries are improved, and high energy density is achieved and fast charging and discharging performance.

CN119230760APending Publication Date: 2024-12-31TSINGHUA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411279513.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The lithium metal negative electrode has problems with dendrite growth and dead lithium accumulation under high-rate charging and discharge conditions, resulting in limited battery cycle stability and life, making it difficult to achieve high energy density and fast charging and discharge performance.

Method used

By modifying the nanovanadiode-based lithium-philic material on the skeleton interface, a body-center cubic structure shared by vanadium metal and lithium metal is formed, and the uniform growth of lithium metal along the Li(110) plane is regulated, dendrites are inhibited and volume expansion is expanded, and solid electrolytes are improved Stability of interface mask.

Benefits of technology

It significantly improves the high-rate cycle stability and cycle life of lithium metal negative electrodes, and provides market competitiveness under high energy density and fast charging and discharge conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230760A_ABST
    Figure CN119230760A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: carrying out coating modification treatment on a framework material and a vanadium-based precursor so as to obtain a framework material loaded with a vanadium-based lithium-loving substance; and mixing the framework material loaded with the vanadium-based lithium-loving substance with metal lithium so as to obtain the vanadium-based lithium-loving composite framework lithium metal negative electrode. The method is easy to operate, the lithium metal negative electrode obtained through the method has the effects of inducing lithium metal to grow crystal faces, inhibiting lithium dendrite growth and modifying solid electrolyte interfacial film components, the high-rate cycle stability of the lithium metal negative electrode is remarkably improved, and the cycle life of the lithium metal negative electrode is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a vanadium-based lithium-philic composite skeleton lithium metal negative electrode and a preparation method thereof. Background Art

[0002] Metallic lithium has a very high theoretical specific capacity (3860mAh / g), which can be matched with a high-capacity positive electrode; it has an extremely low electrochemical potential (-3.04V vs. standard hydrogen electrode), which can expand the operating voltage of the battery and thus achieve a higher theoretical energy density.

[0003] In lithium metal anodes, as the current density increases, the unevenness of lithium ion flux in different areas of the lithium anode surface gradually increases, and the macroscopic phenomenon manifested transitions from polarization problems at low current density to internal short circuit problems caused by dendrites at high current density. In addition, the high reactivity of lithium metal creates an unstable electrode interface, and its host-free structure also forms a large volume change during the deposition and release process, resulting in an irreversible increase in dead lithium. With the deepening of basic research in the past decade, the practical application of lithium metal anodes is still difficult.

[0004] In order to realize the practical application of lithium metal anode, it is necessary to achieve high energy density (>350Wh / kg) and fast charging and discharging performance (<15min), which requires lithium metal anode to have high cycle capacity (>5mAh cm -2 ), high lithium utilization (>50%) and high current density (>20mA cm -2 ) operating under harsh conditions. The unbalanced electron exchange rate and ion transfer rate limit the fast charge and discharge performance of lithium metal anodes. How to kinetically regulate the electron gain and loss / ion transfer process in the system to achieve long-life cycles under fast charge and discharge conditions is a problem that restricts the practical application of lithium metal batteries. Summary of the invention

[0005] The inventors found that due to the order of magnitude difference in the time constants of electron transfer and ion transport at the skeleton interface, lithium metal is easily deformed and bifurcated to form dendrites during high-rate charge and discharge, and causes serious top blockage and dead lithium accumulation under large-capacity conditions. In this case, it is difficult for lithium metal to circulate stably under fast charge and discharge and high energy density.

[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. The inventors have found some effective methods to inhibit lithium dendrites through experimental exploration, mainly focusing on crystal plane adjustment, interface protection and skeleton design. The nano-vanadium-based lithium-philic material is modified in the skeleton to construct the "host" structure of the lithium metal negative electrode, provide space restrictions, inhibit the local stress changes of lithium deposition and release, and improve the growth and volume expansion of lithium metal dendrites. The nano-vanadium-based lithium-philic material can react with lithium metal to form vanadium metal, forming V (110) crystal plane sites dispersed inside the skeleton, inducing lithium metal to grow uniformly and densely along the Li (110) plane, which can inhibit the growth of lithium dendrites, improve the stability of the solid electrolyte interface film, and significantly improve the high-rate cycle stability and cycle life of the lithium metal negative electrode.

[0007] In the first aspect of the present invention, the present invention proposes a method for preparing a vanadium-based lithium-philic composite skeleton lithium metal negative electrode. According to the embodiment of the present invention, the method comprises: coating and modifying the skeleton material and the vanadium-based precursor to obtain the skeleton material loaded with vanadium-based lithium-philic substances; mixing the skeleton material loaded with vanadium-based lithium-philic substances with metallic lithium to obtain the vanadium-based lithium-philic composite skeleton lithium metal negative electrode. The method according to the embodiment of the present invention is simple to operate. The method prepares a skeleton modified with a vanadium-based lithium-philic substance by coating and modification. After the skeleton is composited with lithium metal, the (110) face of the body-centered cubic structure shared by vanadium metal and lithium metal is used to regulate the uniform and dense growth of lithium metal along the Li (110) face. The lithium metal negative electrode obtained by this method has the functions of inducing the growth crystal face of lithium metal, inhibiting the growth of lithium dendrites, and modifying the components of the solid electrolyte interface film, which significantly improves the high-rate cycle stability and cycle life of the lithium metal negative electrode.

[0008] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0009] According to an embodiment of the present invention, the vanadium-based lithium-philic substance is a nano-sized vanadium-based lithium-philic substance.

[0010] According to an embodiment of the present invention, the skeleton material is a skeleton material composed of one or more selected from carbon-based materials, metal-based materials and other conductive materials.

[0011] According to an embodiment of the present invention, the skeleton material is a porous skeleton material having a structure of fiber, foam, array, network, aerogel, etc.

[0012] According to an embodiment of the present invention, the carbon-based material is selected from graphite, fullerene, graphene, graphyne, carbon nanofiber, carbon nanotube, carbon cloth, carbon paper, biomass-derived carbon or a functional surface-modified carbon material derived from the above materials.

[0013] According to an embodiment of the present invention, the metal-based material is selected from vanadium, iron, cobalt, nickel, copper, aluminum, platinum, gold, silver, tin and alloys thereof.

[0014] According to an embodiment of the present invention, the other conductive materials are selected from conductive polymer materials, metal organic framework materials (MOF), and transition metal carbon / nitride two-dimensional nano-layered materials (MXene).

[0015] According to an embodiment of the present invention, the vanadium-based precursor is a substance containing vanadium element and capable of in-situ generating vanadium-based lithium-philic substances on a framework material.

[0016] According to an embodiment of the present invention, the vanadium-based lithium-philic substance is one or more of metallic vanadium and / or a vanadium-based compound that can react with lithium to form metallic vanadium.

[0017] According to an embodiment of the present invention, the vanadium-based compound is vanadium oxide, vanadium fluoride, vanadium chloride, vanadium sulfide, vanadium bromide, vanadium iodide, vanadium carbide or vanadium nitride.

[0018] According to an embodiment of the present invention, the mixing process further comprises drying the framework material loaded with the vanadium-based lithium-philic substance.

[0019] According to an embodiment of the present invention, the drying process is one or more processes selected from natural drying, forced air drying, vacuum drying, heating drying, and freeze drying.

[0020] According to an embodiment of the present invention, the metallic lithium is liquid metallic lithium.

[0021] According to an embodiment of the present invention, the mixing treatment is performed by placing the framework material loaded with the vanadium-based lithiophilic substance into liquid metallic lithium for immersion treatment.

[0022] According to an embodiment of the present invention, the temperature of the liquid metal lithium is 190-600°C.

[0023] According to an embodiment of the present invention, the immersion treatment time is 5 to 600 seconds.

[0024] According to an embodiment of the present invention, the coating modification treatment is one or more treatments selected from the group consisting of immersion, magnetron sputtering, electroplating, solvent thermal treatment, liquid phase chemical deposition, and high temperature calcination.

[0025] According to an embodiment of the present invention, the coating modification treatment is carried out in the following manner:

[0026] 1) dissolving the vanadium-based precursor with a mixed solution of water / ethanol to obtain a dissolved mixed solution;

[0027] 2) adjusting the pH of the dissolved mixture to 2 to obtain an acidic dissolved mixture;

[0028] 3) Immersing the framework material in the acidic dissolving mixture to obtain the framework material loaded with the vanadium-based lithium-philic substance.

[0029] According to an embodiment of the present invention, the immersion is performed in a hydrothermal reactor with a polytetrafluoroethylene liner.

[0030] According to an embodiment of the present invention, the immersion temperature is 180°C.

[0031] According to an embodiment of the present invention, the immersion time is 18 hours.

[0032] According to an embodiment of the present invention, the content of ethanol in the water / ethanol mixed solution is 10 vol%. The inventors found that if the content is not this, the penetration of lithium metal and the subsequent charge and discharge cycle of lithium metal will be blocked.

[0033] According to an embodiment of the present invention, the usage ratio of the vanadium-based precursor to the water / ethanol mixed solution is 0.3 g:75 mL.

[0034] According to an embodiment of the present invention, the vanadium-based precursor is ammonium metavanadate.

[0035] According to an embodiment of the present invention, the coating modification treatment is carried out in the following manner:

[0036] The framework material is immersed in the vanadium-based precursor and thiourea, and subjected to a first heating treatment, a rinsing and drying treatment, and a second heating treatment, so as to obtain the framework material loaded with the vanadium-based lithium-philic substance.

[0037] According to an embodiment of the present invention, the mass ratio of the vanadium-based precursor to the thiourea is 1:2.

[0038] According to an embodiment of the present invention, the vanadium-based precursor is ammonium metavanadate.

[0039] According to an embodiment of the present invention, the temperature of the first heat treatment is 180°C.

[0040] According to an embodiment of the present invention, the time of the first heating treatment is 20 hours.

[0041] According to an embodiment of the present invention, the rinsing and drying processes are performed in air.

[0042] According to an embodiment of the present invention, the temperature of the second heat treatment is 400°C.

[0043] According to an embodiment of the present invention, the duration of the second heating treatment is 20 hours.

[0044] According to an embodiment of the present invention, the coating modification treatment is carried out in the following manner:

[0045] The vanadium-based precursor and thioacetamide are dissolved in a water / ethanol mixed solvent, and subjected to heating treatment, cooling treatment, washing treatment and drying treatment to obtain the framework material loaded with the vanadium-based lithium-philic substance.

[0046] According to an embodiment of the present invention, the vanadium-based precursor is Na3VO4·12H2O.

[0047] According to an embodiment of the present invention, the mass ratio of the Na3VO4·12H2O to the thioacetamide is 1.2:1.1.

[0048] According to an embodiment of the present invention, the temperature of the heating treatment is 180°C.

[0049] According to an embodiment of the present invention, the heating treatment time is 20 hours.

[0050] According to an embodiment of the present invention, the drying process is performed under vacuum conditions at a temperature of 60°C.

[0051] In another aspect of the present invention, the present invention also proposes a vanadium-based lithium-philic composite skeleton lithium metal negative electrode. According to an embodiment of the present invention, the vanadium-based lithium-philic composite skeleton lithium metal negative electrode is prepared by the method described above. The lithium metal negative electrode according to the embodiment of the present invention has the functions of inducing lithium metal growth crystal planes, inhibiting lithium dendrite growth, and modifying the solid electrolyte interface film components, which significantly improves the high-rate cycle stability and cycle life of the lithium metal negative electrode.

[0052] According to the embodiments of the present invention, the present invention has at least one of the following technical effects:

[0053] 1) According to an embodiment of the present invention, a skeleton modified with a vanadium-based lithium-philic compound is prepared by simply modifying the surface of the original skeleton material by coating. After the skeleton is composited with lithium metal, the (110) plane of the body-centered cubic structure shared by vanadium metal and lithium metal is used to regulate the uniform and dense growth of lithium metal along the Li (110) plane.

[0054] 2) The preparation method according to the embodiment of the present invention has a simple mechanism, a simple process and simple operation.

[0055] 3) According to the embodiments of the present invention, the negative electrode material obtained by the present invention has excellent rate performance and cycle stability at high rate and large capacity when applied to the negative electrode of a lithium metal battery, which provides market competitiveness for lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0057] Figure 1 is the XRD data of the composite electrode prepared in Example 1;

[0058] Figure 2 is 50 mA cm in Example 1 -2 Current density, 1mAh cm -2 Charge and discharge curve diagram under cycle capacity;

[0059] Figure 3 is 50 mA cm in Example 1 -2 Current density, 5mAh cm -2 Charge and discharge curve diagram under cycle capacity;

[0060] Figure 4 is 50 mA cm in Example 1 -2 Current density, 20mAh cm -2 Charge and discharge curve diagram under cycle capacity;

[0061] Figure 5 is a scanning electron microscope image of Comparative Example 1;

[0062] Figure 6 is a scanning electron microscope image of Comparative Example 2;

[0063] Figure 7 Graphs showing the electrochemical performance of the skeleton-assembled lithium metal negative electrodes of Comparative Example 1 and Comparative Example 2;

[0064] Figure 8 is 50 mA cm in Comparative Example 3 -2 Current density, 1mAh cm -2 Charge and discharge curve diagram under cycle capacity. DETAILED DESCRIPTION

[0065] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0066] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0067] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0068] Example 1

[0069] 1) Preparation of vanadium-based lithium-philic framework materials

[0070] First, 0.30 g of ammonium metavanadate (NH4VO3) was dispersed in a mixed solution of 75 ml of deionized water and ethanol (ethanol content was 10 vol%), magnetically stirred to fully dissolve it, and then the pH value of the solution was adjusted to 2 with 1 mol / L dilute hydrochloric acid. After magnetic stirring, the solution was transferred to a hydrothermal reactor with a 100 ml polytetrafluoroethylene liner.

[0071] The carbon fiber surface was plasma treated to completely immerse it in the above solution. The hydrothermal reactor with a polytetrafluoroethylene liner was placed in an oven and heated at 180°C for 18 hours, and then taken out after cooling to room temperature. The carbon fiber (CNF) loaded with vanadium dioxide (VO2) nanobelts was collected, washed with deionized water for about 5-6 times, and then freeze-dried to obtain a carbon fiber / vanadium dioxide sample.

[0072] 2) Preparation of lithium metal anode and assembly of lithium metal battery

[0073] Metallic lithium is melted into liquid metallic lithium in an argon environment, and the lithiophilic skeleton material is immersed in liquid metallic lithium at 300° C. for about 10 seconds to obtain a composite lithium metal negative electrode. Figure 1 : is the XRD data of the composite electrode prepared in this example. It can be seen from the figure that the Li(110) crystal plane dominates the lithium metal electrode before and after the cycle, and the diffraction peaks of the other two crystal planes are almost negligible.

[0074] In an argon environment, composite lithium metal electrodes were selected as positive and negative electrodes to assemble symmetrical batteries, and tests were performed at different current densities and cycle capacities. The test results are as follows: Figures 2 to 4 shown.

[0075] like Figure 2 As shown, the symmetrical battery can achieve a current density of 50 mA / cm 2 Under the same conditions, the device can stably cycle for more than 1200 cycles, and can still maintain a small overpotential of about 100mV at around 1000 cycles.

[0076] Depend on Figure 3 It can be seen that the symmetrical battery can be 5mAh / cm 2 It can stably cycle for more than 400 times at a large capacity, and there is no obvious increasing trend in the overpotential.

[0077] Depend on Figure 4It can be seen that the symmetrical battery can be used at an ultra-large current density of 50mA / cm 2 And ultra-high surface capacity 20mAh / cm 2 The overpotential has no obvious increasing trend and can be stably cycled for more than 100 times under the condition of

[0078] Example 2

[0079] 1) Preparation of vanadium-based lithium-philic framework materials

[0080] The carbon fiber (CNF) was soaked in 150 mg of NH4VO3 and 300 mg of thiourea and then transferred to a hydrothermal autoclave. The hydrothermal autoclave was heated to 180°C and maintained for 20 hours, then rinsed and dried, and finally heated at 400°C in air for 20 hours to obtain a carbon fiber / vanadium dioxide (CNF / VO2) skeleton.

[0081] 2) Preparation of lithium metal anode and assembly of lithium metal battery

[0082] Metallic lithium is melted at 300°C in an argon environment to form liquid metallic lithium, and a lithiophilic skeleton material is immersed in the liquid metallic lithium for about 10 seconds to obtain a composite lithium metal negative electrode.

[0083] Example 3

[0084] 1) Preparation of vanadium-based lithium-philic framework materials

[0085] First, 0.30 g of ammonium metavanadate (NH4VO3) was dispersed in a mixed solution of 75 ml of deionized water and ethanol (ethanol content was 20 vol%), magnetically stirred to fully dissolve it, and then the pH value of the solution was adjusted to 2 with 1 mol / L dilute hydrochloric acid. After magnetic stirring, the solution was transferred to a hydrothermal reactor with a 100 ml polytetrafluoroethylene liner.

[0086] The carbon fiber surface was plasma treated to completely immerse it in the above solution. The hydrothermal reactor with a polytetrafluoroethylene liner was placed in an oven and heated at 180°C for 18 hours, and then taken out after cooling to room temperature. The carbon fiber loaded with vanadium dioxide nanobelts was collected and heated at 500°C for 3 hours in an NH3 atmosphere to obtain a carbon fiber / vanadium nitride (CNF / VN) sample.

[0087] 2) Preparation of lithium metal anode

[0088] Metallic lithium is melted at 300°C in an argon environment to form liquid metallic lithium, and a lithiophilic skeleton material is immersed in the liquid metallic lithium for 30 seconds to obtain a composite lithium metal negative electrode.

[0089] Example 4

[0090] 1) Preparation of vanadium-based lithium-philic framework materials

[0091] 1.2 g of sodium vanadate dodecahydrate (Na3VO4·12H2O) and 1.127 g of thioacetamide (TAA) were dissolved in a mixed solvent consisting of 25 mL of deionized water and 10 mL of ethanol and stirred evenly. The solution was then transferred to a hydrothermal autoclave and heated at 180 ° C for 20 h. After natural cooling, it was washed three times with deionized water and ethanol respectively. Finally, it was dried under vacuum at 60 ° C to obtain a carbon fiber / vanadium disulfide (CNF / VS2) sample.

[0092] 2) Preparation of lithium metal anode

[0093] Metallic lithium is melted at 300°C in an argon environment to form liquid metallic lithium, and a lithiophilic skeleton material is immersed in the liquid metallic lithium for 30 seconds to obtain a composite lithium metal negative electrode.

[0094] Example 5

[0095] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the skeleton is carbon cloth. The specific steps are as follows:

[0096] 1) Preparation of lithium-philic framework materials

[0097] First, 0.30 g of ammonium metavanadate (NH4VO3) was dispersed in a mixed solution of 75 ml of deionized water and ethanol in a volume ratio of 9:1, and magnetic stirring was used to fully dissolve it. Then, the pH value of the solution was adjusted to 2 with 1 mol / L dilute hydrochloric acid. After magnetic stirring, the solution was transferred to a hydrothermal reactor with a 100 ml polytetrafluoroethylene liner.

[0098] The carbon cloth was treated with a 100W surface plasma for 10 minutes to completely immerse it in the above solution. The hydrothermal reactor with a polytetrafluoroethylene liner was placed in an oven and heated at 180°C for 18 hours, and then taken out after cooling to room temperature. The carbon cloth loaded with vanadium dioxide nanobelts was collected, washed with deionized water for about 5-6 times, and then freeze-dried to obtain a carbon cloth / vanadium dioxide (CC / VO2) sample.

[0099] 2) Preparation of lithium metal anode

[0100] Metallic lithium is melted at 300°C in an argon environment to form liquid metallic lithium, and a lithiophilic skeleton material is immersed in the liquid metallic lithium for 20 seconds to obtain a composite lithium metal negative electrode.

[0101] Example 6

[0102] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the skeleton is carbon paper. The specific steps are as follows:

[0103] 1) Preparation of lithium-philic framework materials

[0104] First, 0.30 g of ammonium metavanadate (NH4VO3) was dispersed in a mixed solution of 75 ml of deionized water and ethanol in a volume ratio of 9:1, and magnetic stirring was used to fully dissolve it. Then, the pH value of the solution was adjusted to 2 with 1 mol / L dilute hydrochloric acid. After magnetic stirring, the solution was transferred to a hydrothermal reactor with a 100 ml polytetrafluoroethylene liner.

[0105] The carbon paper was treated with plasma to completely immerse it in the above solution. The hydrothermal reactor with a polytetrafluoroethylene liner was placed in an oven and heated at 180°C for 18 hours, and then taken out after cooling to room temperature. The carbon paper loaded with vanadium dioxide nanobelts was collected, washed with deionized water for about 5-6 times, and then freeze-dried to obtain a carbon paper / vanadium dioxide (CP / VO2) sample.

[0106] 2) Preparation of lithium metal anode

[0107] Metallic lithium is melted at 300°C in an argon environment to form liquid metallic lithium, and a lithiophilic skeleton material is immersed in the liquid metallic lithium for 20 seconds to obtain a composite lithium metal negative electrode.

[0108] Comparative Example 1

[0109] The preparation method of this comparative example is basically the same as that of Example 1, except that the proportion of ethanol in the solvent is 20 vol%. The specific steps are as follows:

[0110] First, 0.30 g of ammonium metavanadate (NH4VO3) was dispersed in 75 ml of a mixed solution of deionized water and ethanol (ethanol ratio was 20 vol%), magnetically stirred to fully dissolve it, and then the pH value of the solution was adjusted to 2 with 1 mol / L dilute hydrochloric acid. After magnetic stirring, the solution was transferred to a hydrothermal reactor with a 100 ml polytetrafluoroethylene liner.

[0111] The carbon fiber was plasma treated to completely immerse it in the above solution. The hydrothermal reactor with a polytetrafluoroethylene liner was placed in an oven and heated at 180°C for 18 hours, and then taken out after cooling to room temperature. The carbon fiber loaded with vanadium dioxide nanobelts was collected, washed with deionized water for about 5-6 times, and then freeze-dried to obtain a carbon fiber / vanadium dioxide-20% (CNF / VO2-20%) sample.

[0112] Figure 5 This is a scanning electron microscope image of the composite electrode after the skeleton prepared in this comparative example was filled with molten lithium. It can be seen from the figure that the VO2 content on the surface of the skeleton is very small, and it is difficult to make lithium metal evenly penetrate the interior of the skeleton through the contact reaction between VO2 and molten lithium.

[0113] Comparative Example 2

[0114] The preparation method of this comparative example is basically the same as that of Example 1, except that the proportion of ethanol in the solvent is 3.3 vol%. The specific steps are as follows:

[0115] First, 0.30 g of ammonium metavanadate (NH4VO3) was dispersed in a mixed solution of 75 ml of deionized water and ethanol (ethanol ratio was 3.3 vol%), magnetically stirred to fully dissolve it, and then the pH value of the solution was adjusted to 2 with 1 mol / L dilute hydrochloric acid. After magnetic stirring, the solution was transferred to a hydrothermal reactor with a 100 ml polytetrafluoroethylene liner.

[0116] The carbon fiber was plasma treated to completely immerse it in the above solution. The hydrothermal reactor with a polytetrafluoroethylene liner was placed in an oven and heated at 180°C for 18 hours, and then taken out after cooling to room temperature. The carbon fiber loaded with vanadium dioxide nanobelts was collected, washed with deionized water for about 5-6 times, and then freeze-dried to obtain a carbon fiber / vanadium dioxide-3.3% (CNF / VO2-3.3%) sample.

[0117] Figure 6 The scanning electron microscope images of the skeleton prepared in this comparative example and the composite electrode after melt lithium filling are shown in the figure. It can be seen from the figure that VO2 basically covers the entire skeleton, blocking the penetration of lithium metal and the subsequent charge and discharge cycle of lithium metal.

[0118] The electrochemical performance of the skeleton-assembled lithium metal negative electrode of Comparative Example 1 and Comparative Example 2 is as follows: Figure 7 As shown, it can be seen that the coverage of VO2 affects the contact between lithium metal and VO2 during the lithium filling process. Too much or too little coverage will reduce the cycle performance.

[0119] Comparative Example 3

[0120] The battery assembly method of this comparative example is the same as that of Example 1, except that the electrode is not a composite electrode with a skeleton but a pure lithium sheet. The specific implementation method is as follows:

[0121] In an argon environment, lithium metal sheets were selected as the positive and negative electrodes, and symmetrical batteries were assembled. Different current densities and capacities were applied to test the cycle stability of the symmetrical batteries. -2 Current density, 1mAh cm -2 The charge and discharge curve under cycle capacity is as follows Figure 8 As shown, the polarization voltage increased and then decreased repeatedly between 120 and 150 cycles, indicating that the lithium metal interface is unstable and that interface side reactions and short circuits may have occurred.

[0122] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0123] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a vanadium-based lithium-philic composite framework lithium metal negative electrode, characterized in that: include: The skeleton material and the vanadium-based precursor are subjected to coating and modification treatment to obtain the skeleton material loaded with the vanadium-based lithium-philic substance; The skeleton material loaded with the vanadium-based lithiophilic substance is mixed with metallic lithium to obtain the vanadium-based lithiophilic composite skeleton lithium metal negative electrode.

2. The method according to claim 1, characterized in that The vanadium-based lithium-philic substance is a nano-sized vanadium-based lithium-philic substance; Optionally, the skeleton material is a skeleton material composed of one or more selected from carbon-based materials, metal-based materials and other conductive materials; Optionally, the skeleton material is a porous skeleton material having a structure of fiber, foam, array, network, aerogel, etc.; Optionally, the carbon-based material is selected from graphite, fullerene, graphene, graphyne, carbon nanofiber, carbon nanotube, carbon cloth, carbon paper, biomass-derived carbon or a functional surface-modified carbon material derived from the above materials; Optionally, the metal-based material is selected from vanadium, iron, cobalt, nickel, copper, aluminum, platinum, gold, silver, tin and alloys thereof; Optionally, the other conductive material is selected from conductive polymer materials, metal organic framework materials, and transition metal carbon / nitride two-dimensional nano-layered materials.

3. The method according to claim 1, characterized in that The vanadium-based precursor is a substance containing vanadium element and capable of in-situ generating vanadium-based lithium-philic substances on the framework material; Optionally, the vanadium-based lithiophilic substance is one or more of metallic vanadium and / or a vanadium-based compound capable of reacting with lithium to form metallic vanadium; Optionally, the vanadium-based compound is vanadium oxide, vanadium fluoride, vanadium chloride, vanadium sulfide, vanadium bromide, vanadium iodide, vanadium carbide or vanadium nitride.

4. The method according to claim 1, characterized in that: The mixing process includes drying the framework material loaded with the vanadium-based lithium-philic substance before the mixing process; optionally, the drying process is one or more of natural drying, forced air drying, vacuum drying, heating drying, and freeze drying.

5. The method according to claim 1, characterized in that: The metallic lithium is liquid metallic lithium; Optionally, the mixing treatment is performed by placing the framework material loaded with the vanadium-based lithiophilic substance into liquid metallic lithium for immersion treatment; Optionally, the temperature of the liquid metal lithium is 190 to 600° C.; Optionally, the immersion treatment time is 5 to 600 seconds.

6. The method according to claim 1, characterized in that The coating modification treatment is one or more of immersion, magnetron sputtering, electroplating, solvent heat, liquid phase chemical deposition or high temperature calcination.

7. The method according to claim 1, characterized in that The coating modification treatment is carried out in the following manner: Dissolving the vanadium-based precursor with a water / ethanol mixed solution to obtain a dissolved mixed solution; adjusting the pH of the dissolved mixed solution to 2 to obtain an acidic dissolved mixed solution; Immersing the framework material in the acidic dissolving mixture to obtain the framework material loaded with the vanadium-based lithium-philic substance; Optionally, the immersion is carried out in a hydrothermal reactor with a polytetrafluoroethylene liner; Optionally, the immersion temperature is 180°C; Optionally, the immersion time is 18 hours; Optionally, the content of ethanol in the water / ethanol mixed solution is 10 vol%; Optionally, the amount ratio of the vanadium-based precursor to the water / ethanol mixed solution is 0.3 g:75 mL; Optionally, the vanadium-based precursor is ammonium metavanadate.

8. The method according to claim 1, characterized in that The coating modification treatment is carried out in the following manner: The skeleton material is immersed in the vanadium-based precursor and thiourea, and subjected to a first heating treatment, a rinsing and drying treatment, and a second heating treatment, so as to obtain the skeleton material loaded with the vanadium-based lithium-philic substance; Optionally, the mass ratio of the vanadium-based precursor to the thiourea is 1:2; Optionally, the vanadium-based precursor is ammonium metavanadate; Optionally, the temperature of the first heating treatment is 180°C; Optionally, the first heating treatment time is 20 hours; Optionally, the temperature of the second heating treatment is 400°C; Optionally, the second heating treatment time is 20 hours; Optionally, the second heating treatment is performed in air.

9. The method according to claim 1, characterized in that: The coating modification treatment is carried out in the following manner: Dissolving the vanadium-based precursor and thioacetamide in a water / ethanol mixed solvent, and performing heating treatment, cooling treatment, washing treatment and drying treatment to obtain the framework material loaded with the vanadium-based lithium-philic substance; Optionally, the vanadium-based precursor is Na3VO4·12H2O; Optionally, the mass ratio of the Na3VO4·12H2O to the thioacetamide is 1.2:1.1; Optionally, the temperature of the heating treatment is 180°C; Optionally, the heating treatment time is 20 hours; Optionally, the drying process is performed under vacuum conditions at a temperature of 60°C.

10. A vanadium-based lithium-philic composite framework lithium metal negative electrode, characterized in that: The vanadium-based lithiophilic composite skeleton lithium metal negative electrode is prepared by the method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Vanadium disulfide / graphene composite material and preparation method therefor

    CN105355865A

  • Vanadium tetrasulfide sodium-ion battery negative electrode material and preparation method thereof

    CN109599560A

  • Three-dimensional metal lithium-oxide composite negative electrode as well as preparation method and application thereof

    CN115000355A